MANAJEMEN LABA; TANTANGAN MANAJER DI BALIK SUSTAINABILITAS PERUSAHAAN - M. Wahyuddin Abdullah (AkMen JURNAL ILMIAH, 2013)
This writing intent describe manager behaviour does earnings management for sustainability of firm and words manager daring do profit management is turned back sustainability of firm. Earnings management was regarded by conflict of interest among manager and stockholder in keep its prosperity zoom. Accounting theorist agglomerates earnings management to become 2 perspectives, which is opportunistic behavior and efficient contracting, meanwhile manager motivation does earnings management, amongst those bonus scheme, debt convenant, political motivation, taxation motivation , CEO'S commutation (Chief Officers Officer), and Initial Publik Offering (IPO). Earnings management constitutes to run the risk manager work, manager does earnings management to look after sustainability of firm. Earnings management involves manager moral agency. Society not only will entity business have tall finance performance, but also tall ethical performance too. Thus, challenge of manager does earnings management is balance attainment among manager behalf by does bit to the interested partieses on corporate.